Youth Building the Future: An estimate of labor insertion in Mexico and by region - ORTIZ FIGUEROA, ASTRID; REYNOSO, LUIS HUESCA; LLAMASREMBAO, LINDA IRENEA; NEVÁREZ, JOAQUÍN BRACAMONTES (Equilibrio Económico, 2026)
It is common for unemployment to affect young people more, and the regional aspect plays a significant role. In Mexico, strategies have been implemented since 1984, among the most recent, the Youth Building the Future program (JCF for its initials in Spanish). The objective of this work is to determine the effect of labor insertion on the eligible groups of the program and to evaluate its impact at the national and regional levels. The matching technique based on propensity score matching in attributes is employed, using the Mahalanobis distance and the Household Income and Expenditure Surveys (ENIGH) from 2020 and 2022. The databases correspond to the pandemic and post-pandemic periods. The average treatment effect in the eligible groups (ATT and ATE) was estimated. The findings highlight, at the national level, a positive and statistically significant ATE and ATT where 4 out of 10 young people achieve labor insertion, while, by regions, the South-Southeast obtained a level of insertion with 4.4 out of 10 (ATT= 0.44) even though the enrollment of JCF is the highest in participation in this region. While the northern region achieved the highest insertion level, with 5 out of 10 beneficiaries (ATT= 0.536) showing a greater labor absorption capacity in their formal markets.